The Impact of the Development of the Terowongan Nur Mentaya Tunnel Tourist Attraction on the Income of the Surrounding Community - Sari Hayati*; Wahyuni Wahyuni (Universitas Syiah Kuala, 2024)
Local tourism is an economic factor that can be developed as a source of regional income, especially for local communities. The aim of this research is to 1) find out whether the number of tourist visits has an effect on national income, and 2) find out whether the length of stay of tourists has an effect on national income. 3) Find out whether the number of trips affects a person's income. The data used in this research is qualitative data obtained from interviews with respondents. This data was recorded to compare each opinion with the information provided by respondents related to the research questions. The results of this research show that the number of tourist trips is related to the income of the surrounding community, SME owners, as well as length of stay and number of tours, and in general Puncak Tourism Park has been successful. in moving and influencing the economy. We encourage the development of local communities through recruitment and creating business opportunities. BerdLocal tourism is an economic factor that can be developed as a source of regional income, especially for local communities. The aim of this research is to 1) find out whether the number of tourist visits has an effect on national income, and 2) find out whether the length of stay of tourists has an effect on national income. 3) Find out whether the number of trips affects a person's income. The data used in this research is qualitative data obtained from interviews with respondents. This data was recorded to compare each opinion with the information provided by respondents related to the research questions. The results of this research show that the number of tourist trips is related to the income of the surrounding community, SME owners, as well as length of stay and number of tours, and in general Puncak Tourism Park has been successful. in moving and influencing the economy. We encourage the development of local communities through recruitment and creating business opportunities. Based on research findings that the Unchak Tourist Park plays an important role in the economic recovery of the surrounding community, the government should pay more attention to the development of tourism in the Sydenleng Lapang area in the future. is important in the economic recovery of the surrounding community, so the government should pay more attention to the development of tourism in the Baamang area in the future.